RELEVANSI PEMIKIRAN IKHWAN AL-SHAFA BAGI PENGEMBANGAN DUNIA PENDIDIKAN - Furqon Syarif Hidayatullah (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2013)
Ikhwan Al-Shafa is a wellknown person in education. His theory of education is very relevant to recent theory of education. He also proposed the aim of education, law of learning curricullum, method of teaching-learning and the profile of education and student.